Study of the Identity Elements of Cilegon City and Their Influence on Urban Spatial Development - Utami, Nur Kharismawati; Nugraheni, Christanti; Lukman, Muhammad (TERRACE: JOURNAL OF ARCHITECTURE & URBAN STUDIES, 2025)
Cilegon City, located in Banten Province, Indonesia, has characteristics with unique features that are nicknamed the “Steel City”. To emphasize the city's characteristics, it is necessary to study further the “Image of the City” of Cilegon. The influence of city elements (Kevin Lynch) on the development of Cilegon City emphasizes serves as the basis for this research. Research objective Identifying the elements that are characteristic of Cilegon City and understanding how these elements contribute to shaping the overall structure and function of the city. Meanwhile, the methodology of this research uses a descriptive qualitative method with data collection through field observations and literature studies. Research results show that the city image of Cilegon City is good, but there are a few categories that need improvement. Cilegon City has various weaknesses in its urban planning, particularly in terms of spatial fragmentation, traffic congestion, lack of green open spaces, and the impact of industrial areas.